Statistics and political violence: Reflections on the Social Conflict in 2009 in Guadeloupe - Samuel Boris (Coordinamento SIBA, 2014)
In early 2009, Guadeloupe experienced a 44-day strike against the high cost of living and against the illegitimate profits some actors realise in the Island’s economy. Some of these dominant actors being heirs of settlers families, high prices are the starting point for a radical political critique. This article analyses the links between violence and the use of numbers in the course of the conflict. The mobilisation was a time of violence, clashes, and intimidation; but the denunciation of abuse also ascribes a central role to quantification, in order to estimate profit. This article shows how the figures comprise an instrument of mediation being used as a substitute for, or in combination with, multifaceted violent actions. It also shows that the figures may be themselves coercive techniques, playing a part in violent relationships. Quantification can therefore be combined, in a plurality of ways, with the transition to violence, not only by avoiding or replacing it, but sometimes overlapping with it or being its instrument